Dysoticans F–H: three unprecedented dimeric cadinanes from Dysoxylum parasiticum (Osbeck) Kosterm. stem bark. Issue 14 (22nd March 2023) - Naini, Al Arofatus; Mayanti, Tri; Maharani, Rani; Fajriah, Sofa; Kabayama, Kazuya; Shimoyama, Atsushi; Manabe, Yoshiyuki; Fukase, Koichi; Jungsuttiwong, Sirriporn; Supratman, Unang
Abstract : Dysoxylum parasiticum 's stem bark produces an asymmetrical and two symmetrical dimers (1–3 ), dysoticans F–H, with a novel cadinene dimer skeleton. Abstract : An asymmetrical true-dimeric cadinane via ketonic bridge [C-15/C-3′], dysotican F (1 ), two symmetrical pseudo-cadinane dimers through an O -ether linkage [C-3/C-3′], dysoticans G (2 ) and H (3 ), as well as three known sesquiterpenoids 4–6 were obtained from the stem bark of Dysoxylum parasiticum (Osbeck) Kosterm. (Meliaceae). Their structures were determined by spectroscopic and quantum chemical calculations of 13 C NMR shifts using a GIAO method and electronic circular dichroism (ECD) using a TDDFT method. A possible biogenetic pathway for 1–3 beginning from the known compounds (i–ii ) was proposed. Cytotoxic evaluation showed that 2 as a new lead compound is the most potent against the MCF-7 and HeLa cell lines with IC50 values of 12.07 ± 0.17 μM and 9.29 ± 0.33 μM, while 1 has moderate inhibition with IC50 values of 31.59 ± 0.34 μM and 27.93 ± 0.25 μM. Furthermore, 3 is a selective inhibitor against the HeLa cell growth with an IC50 value of 39.72 ± 0.18 μM. A brief structure–activity relationship analysis of all isolated compounds 1–6 was also provided, including comparison with the coexisting molecules in the previous report.